Cardiovascular reactivity during conversations about discrimination is buffered by social support among U.S. Latines - Hannah I. Volpert-Esmond; Jessica R. Bray; Samantha M. Pages; Chad Danyluck (Scientific Reports)
Abstract Racial discrimination is conceptualized as an acute and chronic stressor. Like other acute stressors, lab-based studies demonstrate acute effects of discrimination-related stressors on stress-related cardiovascular outcomes, including total cardiac output, blood pressure, and indices of sympathetic and parasympathetic nervous system activity. Critically, it is important to understand how individual and social factors buffer the experience of race-related acute stress. The current study extends existing work by measuring cardiovascular indices of stress during conversations about racial/ethnic discrimination and examines the moderating role of social support. Latine/Hispanic participants (N = 97) talked about personal discrimination experiences with either a close other or a research assistant they had never previously met. Participants in both conditions exhibited cardiovascular reactivity indicative of stress during the conversation. Additionally, patterns of reactivity reflected a more adaptive stress response and recovery profile when participants talked about discriminatory experiences with a close other relative to a stranger (less parasympathetic withdrawal during the stressor and more parasympathetic rebound during recovery). These patterns are consistent with a stress buffering account of social support, which suggests social bonds and community-level support are critical to consider in interventions to mitigate the harms of experiencing discrimination and prevent chronic health disparities.